Dendrochronology reveals different effects among host tree species from feeding by Lycorma delicatula (White) - Dechaine, Andrew C.; Pfeiffer, Douglas G.; Kuhar, Thomas P.; Salom, Scott M.; Leskey, Tracy C.; McIntyre, Kelly C.; Walsh, Brian; Speer, James H. (Frontiers in Insect Science, 2023)
Spotted lanternfly, Lycorma delicatula (White) (Hemiptera: Fulgoridae), was first detected in the United States in Berks County, Pennsylvania in 2014. Native to China, this phloem-feeding planthopper threatens agricultural, ornamental, nursery, and timber industries in its invaded range through quarantine restrictions on shipments as well as impacts on plants themselves. Long-term impacts of L. delicatula feeding on tree species have not been well studied in North America.Using standard dendrochronological methods on cores taken from trees with differing levels of L. delicatula infestation and systemic insecticidal control, we quantified the impact of L. delicatula feeding on annual growth of four tree species in Pennsylvania: Ailanthus altissima, Juglans nigra, Liriodendron tulipifera, and Acer rubrum. Results suggest that L. delicatula feeding was associated with diminished growth of A. altissima, but no change was observed in any other tree species tested. Results also suggest that systemic insecticides mitigate the impact of L. delicatula feeding on A. altissima growth.